2001
DOI: 10.1177/02750740122064992
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Motivation and Job Performance

Abstract: Perry and Wise (1990) argued that people with high public service motivation (PSM) are more likely than others to choose government jobs, to perform better on the job, and to respond more to nonutilitarian incentives once in government. Using multiple regression and logit analyses on responses by 35,000 federal, white-collar employees to the 1991 Survey of Federal Employees and the 1996 Merit Principles Survey, this article tests the link between PSM and job performance in the federal service. There is mixed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
334
4
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(367 citation statements)
references
References 27 publications
21
334
4
8
Order By: Relevance
“…This means that if the motivation is high, the employees' performance will also be higher. This results support the results of previous research by Asim (2013), Ali et al (2012), Chaudary et al (2012), Laniwidyanti, et al (2010), Koesmono (2006), Sutanto and Patty (2014), Alonso and Lewis (2001) that argued that motivation significantly influences employees' performance. Employees who feel that the company has been able to meet their basic needs (such as food, clothing, housing, and ensure the safety and security of his career) are still highly motivated employees.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This means that if the motivation is high, the employees' performance will also be higher. This results support the results of previous research by Asim (2013), Ali et al (2012), Chaudary et al (2012), Laniwidyanti, et al (2010), Koesmono (2006), Sutanto and Patty (2014), Alonso and Lewis (2001) that argued that motivation significantly influences employees' performance. Employees who feel that the company has been able to meet their basic needs (such as food, clothing, housing, and ensure the safety and security of his career) are still highly motivated employees.…”
Section: Discussionsupporting
confidence: 92%
“…Koesmono (2006), Alonso and Lewis (2001), Ali et al (2012), Chaudary et al (2012), and Asim (2013) all have consistently stated that the motivation affects the employees' performance of employees in a positive correlation. It means that the higher the employees' motivation, the higher their performance.…”
Section: Research Hypothesismentioning
confidence: 98%
“…A study by Kiruja and Mukuru (2013) found that most of the time workers are not happy with their salary and working environment, but Crewsen (2010) confirmed that in the public sector there was the influence of the rewards on employees' motivation and behavior which need not be true in the private sector. Managers from different organizations face different kind of challenges towards satisfying the needs of their employees so as to motivate them and enhance their job performances (Alonso and Lewis, 2001). To summarize, the monetary incentive in its various forms encourages employees to be more productive and self-motivating towards the welfare of the organization they belong.…”
Section: Review Of Literaturementioning
confidence: 99%
“…On the other hand, a number of studies have also shown that public and private sector employees assign equal values to intrinsic rewards and earnings or other extrinsic rewards (e.g., Lyons, Duxbury, and Higgins 2006;Maidani 1991). Recent studies, investigating the role that extrinsic rewards play in sorting individuals into different employment sectors, find that higher earnings are still preferred to lower earnings, even among individuals with PSM who can still value, and be motivated by, financial rewards (e.g., Alonso and Lewis 2001;Christensen and Wright 2009;Rainey 1982;Wittmer 1991;Wright 2007;Wright & Pandey 2008;Vandenabeele 2008). Yet, whether it is the public sector causing individuals to exhibit behavior consistent with PSM or whether it is simply that public service motivated individuals who are drawn into the public sector remains an open empirical question.…”
Section: Related Literaturementioning
confidence: 99%